Effective prophylaxis against rotavirus diarrhea using a combination of Lactobacillus rhamnosus GG and antibodies - Pant, Neha (BioMed Central, 2007)
BACKGROUND: Rotavirus is a worldwide cause of infectious infantile diarrhea that claims over 600,000 lives annually. Recently, two new vaccine candidates have been developed but their efficacy in developing countries, still remains to be proven. Oral delivery of specific immunoglobulins provides passive immunity and is a fast acting treatment for rotavirus diarrhea. Probiotic bacteria have also gained considerable attention lately as treatment for rotavirus diarrhea. Here we report an evaluation of the therapeutic potential of different probiotics and their combination with anti – rotavirus antibodies in a mouse model of rotavirus diarrhea. RESULTS: Of the six probiotic bacteria tested, Lactobacillus rhamnosus strain GG had the strongest influence in reducing prevalence, duration and severity of diarrhea and was therefore chosen for combination treatment with immunoglobulins. The combination treatment reduced the diarrhea outcome measures significantly, prevented histopathological changes and reduced the virus load in the intestines. CONCLUSION: The advantages associated with immunoglobulins and probiotics based therapy is that the treatment provides a rapid therapeutic effect and is cost efficient. These components do not require special storage conditions and could potentially complement the rehydration therapy that is currently used.